Struktur Komunitas Ikan Kepe-Kepe Di Daerah Terumbu Karang Pantai Liang Pulau Bunaken Sulawesi Utara - Youdy Joseph Hendrik Gumolili; Maykel A.J. Karauwan; Jeanlly A Solang (HOSPITALITI DAN PARIWISATA, 2022)
This research was carried out in the coral reef Liang Beach area of Bunaken Island in July 31st 2021 by using the visual cencus method on 5 meters depth. The result of the research showed that there were about 12 species of indicator fish Chaetodontidae are found in the coral reefarea.